“For a Moment I Feel Free”: Homeless Women and a Garden-Based Learning Program - Cathy A. Pierce; Mary F. Ziegler (Adult Education Research Conference, 2008)
Loss of one’s home, conditions of shelter life, and abuse that often precipitate homelessness result in diminished self-efficacy and hope. Adult education programs for homeless women often follow a remedial rather than a developmental model. This mixed method study investigated a unique program in garden-based learning for homeless women to better understand how this type of adult education program contributed to the women’s hope and self-efficacy.
Keywords: garden-based learning; homeless women; hope; self-efficacy